Integrating Exempt Values Inside The Family To Prevent Fraud - Muhammad Ubaidillah; I’ana Umma; Muhammad Wildan Sholih (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
Fraud is a serious problem in the business world. Fraud includes three main things, namely assets misappropriation, faudulent statement and corruption. Various efforts have been made in the framework of prevention. However, fraud still exists today. On the other hand, the family has the potential and an important role in shaping one's character. There are various positive values that can be instilled in children in family institutions. The problem is, many families are now just a mere formality. In fact, parents can educate their children to become anti-fraud individuals, one of which is by setting an example for their children. Therefore, this article proposes a new concept that combines the previous concepts. The concept is to instill exemplary values in the family to prevent fraud. This study uses descriptive analysis to propose the concept of cultivating exemplary values in the family to prevent fraud. This study uses a library research approach to collect secondary data from journal articles, books, reports, and websites that contain the existing concepts of exemplary values and fraud prevention. It is hoped that this formulation can actually reduce fraud that occurs later.